Wartości narodowe a konkurencyjność Japonii - Figuła, Jerzy (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article characterizes Japan’s national values and shows the way they shape up the competiveness of its economy. The author reaches the conclusion that nations achieve a high level of competitiveness as long as they have a culture based on national values conducive to rising to the challenges of world’s economy. Japan’s competitiveness arises from religious and philosophical values: Shintoism, Confucianism, Zen Buddhism. Those systems have formed cultural values and the society of Japan, and endowed it with the qualities of discipline and righteousness, a drive towards self-improvement — kaizen, leading to an ideal organization and ambition of perfectionism. An egalitarian, frugal and non-material society aiming at co-operation has emerged. The family is a cornerstone of the competiveness of Japanese economy, it shapes up and releases the power of the collective. On the basis of the values of the family/collective the following have been built: relationships among employees within a group, lifelong contracts, ways of promotion and remuneration, involvement of employees in companies, quality circles and clustering production runs into nests. The power of the collective is where the keiretsu organization originates, strengthening the structure of the holding through the mutual ownership of shares, broad areas of co-operation and internal fi nancing. Also small and medium enterprises absorbed by the structure of a Japanese company are among the strongest in the world thanks to the high requirements set for them by global Japanese concerns
Keywords: konkurencyjność gospodarki; organizacja przedsiębiorstw; zarządzanie przedsiębiorstwem